PEMBEKALAN ANAK PUTUS SEKOLAH DENGAN PENDIDIKAN ISLAM DALAM MENGHADAPI DUNIA GLOBAL - M. Isnando Tamrin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Children drop out of school in common sense will have an impact on the increasing number of unemployment. Committing criminal acts such as theft, robbery, murder, and others could have been carried out by unemployed school dropouts because they were urged by the necessities of life that continues to increase which encouraged them to do so. Finally, making the community disturbed and peace that has taken root amid the community will disappear. This condition certainly attracts interest for all walks of life, because indeed from year to year, various criminal acts also contribute to eradicating the joints of humanity of the nation's generation in this global era and the growth of chronic and acute syndromes in the human person in various aspects, both morally, ideology, paradigm, cultural and so on. Therefore, Islamic education is expected to be able to play a role in increasing the dignity of the community through awareness of education. Public awareness of education will be the forerunner of the existence of life. However, now there are still many people who are unable to get an education and some have received education (or dropped out of school) but do not have a proper place in the community (unemployed).